Low Temperature (180°C) Growth of Smooth Surface Germanium Epilayers on Silicon Substrates Using Electron Cyclotron Resonance Chemical Vapor Deposition - Teng-Hsiang Chang; Chiao Chang; Yen-Ho Chu; Chien-Chieh Lee; Jenq-Yang Chang; I-Chen Chen; Tomi T. Li (International Journal of Photoenergy)
This paper describes a new method to grow thin germanium (Ge) epilayers (40 nm) on c-Si substrates at a low growth temperature of 180°C using electron cyclotron resonance chemical vapor deposition (ECR-CVD) process. The full width at half maximum (FWHM) of the Ge (004) in X-ray diffraction pattern and the compressive stain in a Ge epilayer of 683 arcsec and 0.12% can be achieved. Moreover, the Ge/Si interface is observed by transmission electron microscopy to demonstrate the epitaxial growth of Ge on Si and the surface roughness is 0.342 nm. The thin-thickness and smooth surface of Ge epilayer grown on Si in this study is suitable to be a virtual substrate for developing the low cost and high efficiency III-V/Si tandem solar cells in our opinion. Furthermore, the low temperature process can not only decrease costs but can also reduce the restriction of high temperature processes on device manufacturing.